IMPACT OF COVID-19 PANDEMIC ON SOCIAL SECURITY IN NIGERIA - SOPKO, JOSEPH TARZA; IJIRSHAR, VICTOR USHAHEMBA; ASOM, SIMEON TERWUAH (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
The study examines the impact of the COVID-19 pandemic on social security in Nigeria. Survey research design was used and data were collected from 1023 respondents comprising of 425 SME owners and 598 employees through a simple random sampling technique. Descriptive statistics and Paired t-test were utilized for the data analysis. The study found that the COVID-19 pandemic has affected the social security of the employees in Nigeria negatively. Due to the COVID-19 pandemic, SMEs significantly laid off many workers and reduced the monthly expenditure on the welfare of workers, and worsened the state of social security among employees. Therefore, the study suggested that the Nigerian government should fully implement the support schemes formulated to cushion the effect of the COVID-19 pandemic and to offer grants for those who have lost employment in the course of this pandemic and improve the household consumption loans to smoothen the consumption pattern during the COVID-19 pandemic. The study also recommends that the Nigerian government should set up a Social Security Trust Fund from which the benefits can be explored during a pandemic or sudden economic hardships and pass a Social Security Act to back up the establishment of the social security fund that would generate funds for any economic hardships or pandemics.